The adaptation of non-standard labour markets and their spatial distribution: the effects and legacies of COVID-19 on South Africa's freelance creative workers - Drummond, Fiona Jane (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Access restricted. Expected release in 2026.
Keywords: Uncatalogued